2020
DOI: 10.3390/nu12092516
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nutritional Supplementation Affects the Dietary Intake and Body Weight of Head and Neck Cancer Patients during (Chemo) Radiotherapy

Abstract: Considering the symptoms of (chemo) radiotherapy and the reduction in food intake in head and neck cancer (HNC) patients, this study aimed to investigate the association between treatment time points and oral nutritional supplementation (ONS) on dietary intake to estimate the frequency of energy and nutrient inadequacy, and also to evaluate body weight changes (BWC). Dietary intake data of 65 patients were obtained from 24-h dietary recalls and prevalence of inadequacy was calculated before or at the beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Adequate protein intake minimizes the severity of oral mucositis in patients with head and neck cancer undergoing radiotherapy ( 75 ). Early nutritional intervention, including oral feeding, nasogastric tube, gastrostomy, etc., can significantly improve weight loss and interrupt or delay of radiotherapy ( 76 ).…”
Section: Measures That Can Be Takenmentioning
confidence: 99%
“…Adequate protein intake minimizes the severity of oral mucositis in patients with head and neck cancer undergoing radiotherapy ( 75 ). Early nutritional intervention, including oral feeding, nasogastric tube, gastrostomy, etc., can significantly improve weight loss and interrupt or delay of radiotherapy ( 76 ).…”
Section: Measures That Can Be Takenmentioning
confidence: 99%
“…• Due to cancer therapy side effects and inadequate dietary intake by many patients, the American Institute for Cancer Research (AICR), American Cancer Society (ACS) (19) and the European Society for Clinical Nutrition and Metabolism-(ESPEN) (13) support the use of a multivitamin-multimineral supplement in doses close to the recommended dietary allowance. High doses of vitamins and minerals are discouraged in the absence of specific deficiencies (13) • Compared to no counselling, individualized dietary counselling showed significant benefits on nutritional status and QOL (p < 0.05) (44) • A prospective observational study with HNC patient during chemo-radiotherapy recommend initiating nutritional counselling in conjunction with prophylactic ONS prescription from diagnosis to adjust the nutrient intake and minimize weight loss (45) • ONS has a lower impact in overcoming nutritional deficiencies in cancer patients when provided orally than via enteral nutrition (46) • A meta-analysis of 11 clinical studies indicated that high-protein, omega-3, and PUFA enriched diets have an overall benefit of increasing the bodyweight of patients receiving chemoradiotherapy compared with other types of diets. However, the impact on the reduction of treatment toxicity and survival is limited (47) • Some clinical studies have proven that the use of fish-derived, omega-3 polyunsaturated fatty acids (2 g/day) in individuals with advanced cancer receiving chemotherapy improve appetite, energy intake, body weight, muscle mass, and/or physical activity.…”
Section: Recommendationmentioning
confidence: 99%
“…Ferreira et al [ 35 ] investigated the association between treatment time points and oral nutritional supplementation (ONS) on dietary intake to estimate the frequency of energy and nutrient inadequacy and also to evaluate body weight changes (BWC). Dietary intake data of 65 patients were obtained from 24-h dietary recalls, and prevalence of inadequacy was calculated before or at the beginning (T0), in the middle (T1), and at the end of treatment (T2).…”
Section: The Nutritional Counseling and Oral Nutritional Supplemenmentioning
confidence: 99%
“…Patients receiving ONS showed a lower weight loss. Therefore, the authors strongly recommended initiating nutritional counseling from diagnosis to optimize macronutrient intake in conjunction with prophylactic ONS prescription to adjust micronutrient intake and minimize the weight loss, making it possible to prevent worse prognosis and NS [ 35 ].…”
Section: The Nutritional Counseling and Oral Nutritional Supplemenmentioning
confidence: 99%